The Effect of Motivation and Appraisal on Employee Performance Competency Training Center of The West Java Provincial Manpower and Transmigration Office - Febriadi, Fadli; Junensih, Junensih; Supriyadi, Supriyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Work motivation is the best performance effort given by an employee to achieve maximum standards to the company. Performance appraisal is a management activity to evaluate employee performance behavior and determine subsequent policies. The method used in this research is a survey method, which will collect data from the company by distributing questionnaires or conducting structured interviews as part of the data collection process. This aims to make it easier for respondents to answer than statistical analysis methods. Based on the simple linear regression analysis technique, the influence of performance appraisal (X) on employee performance (Y) can be explained by the following simple linear regression equation: Y = 2.945 + 1.075X. This can be interpreted as follows: if there is no performance appraisal (X0), the value of employee performance is 2.945. If there is a performance appraisal of one unit (X1), the employee's performance will increase by 1.075X. In this study, the author created 20 questionnaire statements for the performance appraisal variable (X), and the calculated r-value from the questionnaire was greater than the r-table value, so the questionnaire was concluded to be valid, with the highest calculated r-value being from questionnaire no. 3, which had a calculated r-value of 0.498